"Whose development? What hegemony? Tackling the structural dynamics of global social injustice.". Issue 4 (29th November 2019) - Azmanova, Albena
ABSTRACT: I briefly review the main parameters of the conceptual framework David Ingram builds, and then proceed to test its heuristic power by examining its capacity to address three types of domination (relational, structural and systemic) typical of contemporary capitalism.